Delirium and Cognitive Impairment as Predisposing Factors of COVID-19 Infection in Neuropsychiatric Patients: A Narrative Review - Michele Fabrazzo; Antonio Russo; Alessio Camerlengo; Claudia Tucci; Mario Luciano; Valeria De Santis; Francesco Perris; Francesco Catapano; Nicola Coppola (Medicina, 2021)
SARS-CoV-2 neuroinvasive and neurotropic abilities may underlie delirium onset and neuropsychiatric outcomes. Only a limited number of studies have addressed the potential effect of SARS-CoV-2 infection on mental health so far. Most studies mainly reported the acute onset of mixed neuropsychiatric conditions in patients infected with SARS-CoV-2, characterized by agitated behavior, altered level of consciousness, and disorganized thinking, regardless of psychological or socioeconomic triggering factors. The present narrative review aims to analyze and discuss the mechanisms underlying the neuroinvasive/neurotropic properties of SARS-CoV-2 and the subsequent mental complications. Delirium appeared as a clinical manifestation of SARS-CoV-2 brain infection in some patients, without systemic or multiple organ failure symptoms. A small number of studies demonstrated that neuropsychiatric symptoms associated with COVID-19, initially presenting as a confused state, may subsequently evolve in a way that is consistent with the patients’ neuropsychiatric history. A literature analysis on this topic prevalently showed case reports and case series of patients presenting delirium or delirium-like symptoms as the main outburst of COVID-19, plus a cognitive impairment, from mild to severe, which pre-existed or was demonstrated during the acute phase or after infection. Dementia appeared as one of the most frequent predisposing factors to SARS-CoV-2 infection complicated with delirium. Instead, contrasting data emerged on the potential link between COVID-19 and delirium in patients with cognitive impairment and without a neuropsychiatric history. Therefore, clinicians should contemplate the possibility that COVID-19 appears as delirium followed by a psychiatric exacerbation, even without other systemic symptoms. In addition, cognitive impairment might act as a predisposing factor for COVID-19 in patients with delirium.